2021
DOI: 10.1101/2021.10.22.465397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographic distribution and future expansion ofAedes albopictusin the Democratic Republic of the Congo

Abstract: Aedes albopictus with an Asian origin has been reported from central African countries. The establishment of this mosquito species poses a serious threat as the vector of various infectious diseases. Since information about Ae. albopictus in Democratic Republic of the Congo (DRC) is scarce, we investigated the current distribution of this mosquito species. Based on the factors affecting the distribution, we predicted future distribution. We conduced entomological surveys in Kinshasa and three neighboring ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…2017), and the Democratic Republic of the Congo (Bobanga et al . 2018; Vulu et al . 2021) had reported the presence of Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2017), and the Democratic Republic of the Congo (Bobanga et al . 2018; Vulu et al . 2021) had reported the presence of Ae.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus is increasing through time. Notably, surrounding counties such as Mozambique (Kampango and Abílio 2016;Abílio et al 2018), Tanzania (Patrick et al 2017), and the Democratic Republic of the Congo (Bobanga et al 2018;Vulu et al 2021) had reported the presence of Ae. albopictus at a similar time (2015)(2016).…”
Section: Resultsmentioning
confidence: 99%